2021
DOI: 10.3390/polym13162816
|View full text |Cite
|
Sign up to set email alerts
|

Exohedral Functionalization of Fullerene by Substituents Controlling of Molecular Organization for Spontaneous C60 Dimerization in Liquid Crystal Solutions and in a Bulk Controlled by a Potential

Abstract: A study was carried out on the possibility of orderly and spontaneous dimerization at room temperature of C60 cages in fullerene liquid crystal fullerene dyads (R-C60). For this purpose, dyads with a structural elements feature supporting π-stacking and Van der Waals interactions were tested, due to the presence of terthiophene donors linked through an α-position or dodecyloxy chains. In addition, this possibility was also tested and compared to dyads with shorter substituents and the pristine C60. Research ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Unsubstituted fullerene produces singlet oxygen with very high efficiency [ 11 , 12 , 13 ] but suffers from low absorption in the visible region of the electromagnetic spectrum and low solubility in organic solvents (while being insoluble in water [ 14 ]), which strongly hinders its practical use. It has been shown that both problems can be solved by appropriate functionalization of the fullerene unit [ 11 , 15 , 16 , 17 , 18 , 19 ]. A number of works have shown an enhancement in the optical and photosensitizing properties of fullerene-based photosensitizers.…”
Section: Introductionmentioning
confidence: 99%
“…Unsubstituted fullerene produces singlet oxygen with very high efficiency [ 11 , 12 , 13 ] but suffers from low absorption in the visible region of the electromagnetic spectrum and low solubility in organic solvents (while being insoluble in water [ 14 ]), which strongly hinders its practical use. It has been shown that both problems can be solved by appropriate functionalization of the fullerene unit [ 11 , 15 , 16 , 17 , 18 , 19 ]. A number of works have shown an enhancement in the optical and photosensitizing properties of fullerene-based photosensitizers.…”
Section: Introductionmentioning
confidence: 99%